Trends and evolution in IT governance and system security research: A Bibliometric analysis - Halim, Avicena; Zaman, Syahiduz (Maliki Interdisciplinary Journal, 2024)
This study investigates trends and evolution in research on Information Technology (IT) governance and system security through a bibliometric approach. Data from 200 analyzed articles published between 2014 and 2024 indicate that IT governance is a primary focus in academic literature, with a total of 3079 citations reflecting significant impact in this domain. Network analysis and clustering visualize the complexity of relationships among keywords such as "governance," "framework," and "security," while trend analysis highlights increased attention to emerging concepts like "framework" and "security." These findings emphasize the importance of a multidisciplinary approach to understanding and addressing challenges in IT governance within the context of system security in the digital era.